Silencing Palestine: Limitations on free speech within mental health organizations. (9th September 2019) - Berger, Elizabeth; Jabr, Samah
Abstract: The authors report on episodes in which five professional mental health organizations—for the most part associations for psychoanalysis and psychoanalytically oriented psychotherapy—have covertly tried to silence members who bring attention to the issue of human rights abuses inflicted by the Israeli occupation of Palestine. These various vignettes illustrate how the leadership of these organizations systematically attempts to limit the activism of their members, even in their "free time, " and to forbid the introduction of discussion of Israel/Palestine into their newsletters, meetings, chatrooms, and other organizational venues—despite the fact that these organizations profess their commitment to exploring themes of social justice and to the principle of open dialogue. Implications and recommendations are discussed, particularly the practical need for transparency on the part of our organizations and the intellectual need for a more complete theoretical understanding of the roles of history, ideology, and collective meaning within mental life.